ANALYSIS OF THE MAIN CHARACTERS' MORAL VALUE IN NOVEL BALI GIRL SUKRENI BY A.A. TISNA PANJI - Alifiah Nurahman; Patrisia Cuesdeyeni; Meylala (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2021)
This study aims to describe (1) the form of the moral value of human relations with God (2) the form of the moral value of human relations with oneself (3) the form of the moral value of human relations with other humans in the Sukreni Gadis Bali Novel by A.A. Banner of Tisna. This study uses qualitative methods and types of library research. Based on the results of data analysis of moral values ​​in the novel Sukreni Gadis Bali by A.A. Pandji Tisna analyzed 3 relationships, namely: (1) Human relationship with God (its form: Karma), (2) Human relationship with oneself (its form: dishonest, not opinionated, pessimistic, careless and hasty nature, and sincere), (3) Human relations with other humans (its forms: disloyalty, uncaring attitude, evil plans, kind and forgiving attitude, disrespectful or rude attitude, insulting, helping, favoritism, trust, taking advantage of people, and respecting) .